The psychology of imagination : history, theory, and new research horizons - Wagoner, Brady, 1980-; Brescó de Luna, Ignacio; Awad, Sarah H. (Niels Bohr professorship lectures in cultural psychology., 2016)
This book offers a new approach to imagination which brings its emotional, social, cultural, contextual and existential characteristics to the fore. Fantasy and imagination are understood as the human capacity to distance oneself from the here-and-now situation in order to return to it with new possibilities. To do this we use social-cultural means (e.g. language, stories, art, images, etc.) to conceive of imaginary scenarios, some of which may become real.Imagination is involved in every situation of our lives, though to different degrees. Sometimes this process can lead to concrete products (e.g., artistic works) that can be picked up and used by others for the purposes of their imagining. Imagination is not seen here as an isolated cognitive faculty but as the means by which people anticipate and constructively move towards an indeterminate future. It is in this process of living forward with the help of imagination that novelty appears and social change becomes possible.This book offers a conceptual history of imagination, an array of theoretical approaches, imagination's use in psychologist's thinking and a number of new research areas. Its aim is to offer a re-enchantment of the concept of imagination and the discipline of psychology more generally.